2021
DOI: 10.3390/microorganisms10010079
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization by Extremely Halophilic and Metal-Tolerant Community Members from a Sulfate-Dominated Metal-Rich Environment

Abstract: The adaptation to adverse environmental conditions can lead to adapted microbial communities that may be screened for mechanisms involved in halophily and, in this case, metal tolerance. At a former uranium mining and milling site in Seelingstädt, Germany, microbial communities from surface waters and sediment soils were screened for isolates surviving high salt and metal concentrations. The high salt contents consisted mainly of chloride and sulfate, both in soil and riverbed sediment samples, accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…For S. mirabilis P16B-1, struvite (a magnesium-containing ammonium phosphate) or a nickel phosphate had been observed to be formed earlier ( 47 ). In addition, an ammonium phosphate mineral, nickel struvite, had been described to be formed due to metabolic activity and high local metal concentrations surrounding the cells of other metal-resistant strains isolated in the same former mining area ( 3 , 58 ). The same morphology and color observed here indicated that in S. mirabilis , Ni-struvite is the precipitated mineral as well.…”
Section: Discussionmentioning
confidence: 99%
“…For S. mirabilis P16B-1, struvite (a magnesium-containing ammonium phosphate) or a nickel phosphate had been observed to be formed earlier ( 47 ). In addition, an ammonium phosphate mineral, nickel struvite, had been described to be formed due to metabolic activity and high local metal concentrations surrounding the cells of other metal-resistant strains isolated in the same former mining area ( 3 , 58 ). The same morphology and color observed here indicated that in S. mirabilis , Ni-struvite is the precipitated mineral as well.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of fungal strains was performed with soil samples from a former uranium mining site [ 4 ]. The samples were taken at a location receiving drainage waters from tailings and are specifically rich in Sr and Cs (compare Supplementary Table S1 ) at the former uranium mining and milling site near Seelingstädt, Thuringia, Germany ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After trimming, demultiplexing, denoising, sequence merging, ASV resolving, and chimera removal, analysis and phylogenetic tree reconstruction were performed as described above, adding correlation analyses tools available with R (version 4.2.0). All sequences are available at NCBI Sequence Read Archive under the Bioproject PRJNA784578 [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular mechanisms in mineral formation are known to occur through the production of nucleation molecules, or by changing environmental conditions on a small scale [ 5 , 6 , 7 , 8 , 9 ]. Different molecules are involved as templates for the nucleation of biominerals [ 10 ], including proteins, lipids, or polysaccharides.…”
Section: Introductionmentioning
confidence: 99%